Critical reading in the development of research skills in graduate professors - Suárez-Monzón, Noemí (2020)
In the last decade, education in Ecuador has improved due to the effectiveness of public policies. University legislation has implemented profound changes in the search for quality at all levels, which represents a challenge for the training of teachers. In this sense, the objectives of this study were to identify the research skills that are most difficult to acquire for students in master's education programs in Ecuador, and to explain the role of critical reading in their development. An exploratory study was carried out, using comparative analysis to examine the qualitative data derived from the monographs written by these students; evaluating your performance in presenting such results; likewise, two discussion groups were formed with the same students. The results of this first phase revealed weaknesses in research capacity, which are attributed to deficiencies in a sufficient critical reading to achieve the expected objectives. It is concluded that the use of critical reading is an indispensable precedent for the achievement of complex competences such as research, therefore, it requires an interdisciplinary, methodological, systematic and unified work in the teaching of all the modules that the program covers. © 2020. All Rights Reserved.